Influence of particle size scale on mechanical properties of tailings under high pressure. Issue 2 (4th April 2022) - Pan, Zhenkai; Zhang, Chao; Guo, Xiaogang; Ma, Changkun; Ma, Lei; Gan, Shucheng
Abstract : Particle size has an effect on the mechanical properties of tailings materials. The mechanics and crushing characteristics of tailings at high pressure are a research focus for high tailings dams. Tailings with different particle sizes were tested under laboratory high-pressure triaxial compression. The effect of particle size on the compression characteristics of tailings was studied, along with the strength and deformation of tailings with different particle sizes. Based on particle size distribution, the crushing characteristics of the tailings were quantitatively analysed. A mathematical model for crushing index and tailings strength was established. Under high pressure, shearing contraction failure occurred in the tailings samples. The stress–strain relation of the tailings showed strain softening at low confining pressure and continuous hardening at high confining pressure. The confining pressure at which the stress–strain relation changed from strain softening to strain hardening increased with increased particle size. Due to the higher degree of particle crushing for coarse tailings during the shearing under high pressure, the volume deformation of the coarse samples decreases continuously further. It shows increase in the amount of particle breakage as the confining pressure, but the increase rate decreased with the confining pressure increased. The Box Lucas loading accumulation model was used to describe the change in particle breakage with confining pressure. The peak strength of tailings increased exponentially with the improved relative crushing rate.